2009
DOI: 10.1186/1758-5996-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy

Abstract: Diabetic nephropathy is the leading cause of chronic renal disease and a major cause of cardiovascular mortality. Diabetic nephropathy has been categorized into stages: microalbuminuria and macroalbuminuria. The cut-off values of micro- and macroalbuminuria are arbitrary and their values have been questioned. Subjects in the upper-normal range of albuminuria seem to be at high risk of progression to micro- or macroalbuminuria and they also had a higher blood pressure than normoalbuminuric subjects in the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 180 publications
(210 reference statements)
4
112
0
3
Order By: Relevance
“…Diabetic nephropathy often occurs during the progression of type 2 diabetes. Diabetic nephropathy is pathologically characterised by glomerular hypertrophy and hyperfiltration, thickening of the basement membrane, and accumulation of the extracellular matrix (31,32). Numerous studies have reported that HFD induced metabolic syndrome or DM.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy often occurs during the progression of type 2 diabetes. Diabetic nephropathy is pathologically characterised by glomerular hypertrophy and hyperfiltration, thickening of the basement membrane, and accumulation of the extracellular matrix (31,32). Numerous studies have reported that HFD induced metabolic syndrome or DM.…”
Section: Discussionmentioning
confidence: 99%
“…20 Conflicting data exist about the role of SUA in patients with T2DM; the present study was addressed to evaluate the relation between SUA and hypertension, albumin excretion rate and CKD in a cohort of T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a non-enzymatic glycation of proteins which results in the formation of AGEs due to the hyperglycaemia. These bind to collagen and other proteins that constitute the glomerular basement membrane, thus, making the glomerular barrier more permeable to proteins [15].…”
Section: Urinary Protein Excretionmentioning
confidence: 99%